DjumbaiALA : Contributing to Polyphonic Dialogues across the Middle Passage - Duarte de Souza, Cláudio Manoel; Gruber, Valerie; Mignano, Diana Carolina; Ndi, Gilbert Shang (NAB : News from the Institute of African Studies at the University of Bayreuth, 2019)
Founded five years ago, DjumbaiALA is a network committed to enhancing intercultural conversations and a non-hierarchical co-production of knowledge in the Global South. Diverse researchers, artists and activists from Latin America, Africa and Europe are contributing to this cause.